2015
DOI: 10.5604/12321966.1196855
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of seroprevalence against <i>Coxiella burnetii</i> in a sample of farm workers in Western Sicily

Abstract: The results obtained, although based on a small sample, suggest that the disease is present in the territory of Western Sicily, both in animals and in humans. A closer collaboration between doctors and veterinarians is therefore necessary to fight against the spread of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The remaining 7 papers were eventually included in qualitative and quantitative analysis (2.2% of the initial sample). The retrieved studies (range: 2006-2022) [13,14,18,25,26,36,37] included a total of 16 estimates from occupational settings and 3 reference groups. Of the aforementioned studies, 3 were based on immunofluorescence assay (IFA), 3 on enzyme-linked immunoassay (ELISA), and one complement fixation test (CFT).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 7 papers were eventually included in qualitative and quantitative analysis (2.2% of the initial sample). The retrieved studies (range: 2006-2022) [13,14,18,25,26,36,37] included a total of 16 estimates from occupational settings and 3 reference groups. Of the aforementioned studies, 3 were based on immunofluorescence assay (IFA), 3 on enzyme-linked immunoassay (ELISA), and one complement fixation test (CFT).…”
Section: Resultsmentioning
confidence: 99%
“…Alternative sources, such as contaminated manure, wildlife reservoirs and sheep flocks that migrate over longer distances and have been shown to carry C. burnetii in clinically inconspicuous animals, may have contributed to human infections in the German border region, but these phenomena would not explain the geographical distribution observed (Hermans, Jeurissen, Hackert, & Hoebe, ; Hilbert et al, ; Webster, Lloyd, & Macdonald, ). While reports of Q fever in livestock in the German border region during the study period may implicate cattle as potential sources, a recent study found that human contact with sheep and goats, rather than cattle, was a consistent risk factor in human outbreaks (Georgiev et al, ; Verso et al, ). Goat and sheep densities in the German cross‐border area, however, were rather low (see Table ).…”
Section: Discussionmentioning
confidence: 95%
“…This phenomenon is mirrored by a growing number of studies where seroprevalence rates in the population exceed reported cases of symptomatic Q fever. One such study from Denmark showed a rate of 64% of asymptomatic primary infections, while a study from Italy reported 30 seropositive individuals with no related episodes of respiratory or febrile disease (Bacci et al, 2012;Verso et al, 2016). A recent study from Spain found fever-usually considered the hallmark of symptomatic infection-to be absent in almost a third of 39 Q fever positive cases, even though all cases without fever had pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of this pathogen DNA in three of the screened camels indicates the circulation of an abortion-causing pathogen that may have also implications on human health, being a zoonotic agent responsible for Q fever [51,52]. Several serological studies on Coxiella burnetii have been carried out in camels in several countries, reporting a seroprevalence of 40.7% in Egypt [53], 28.7% in Iran [54], 46% in Kenya [55], and 73% in Chad [56].…”
Section: Discussionmentioning
confidence: 99%